CORRELATION STUDIES ON WEEDS AND TUBER YIELD IN POTATO - Panghal, V. S.; Nehra, B. K.; Khurana, S. C.; Singh, Narendra (Potato Journal, 2013)
Two experiments on chemical weed control in potato cultivar Kufri Badshah were conducted during autumn season of 2001-2002 and 2002-2003 at Hisar. Total tuber yield was related to number and dry weight of weeds recorded at 30, 60, and 90 days after planting (DAP), number and yield of A (>125g), B (>75-125g), C (>25-75g) and D (<25g) grade tubers and total tuber number in both the experiments were recorded separately during both these years. Dry weight and number of weeds recorded at 30, 60 and 90 DAP had negative and significant correlation with the total tuber yield. It shows that data on weed population recorded at 30 or 60 DAP can give clear indication of the final tuber yield to be obtained if the weeds are not removed during the crop season. Yield as well as number of A and B grade tubers had positive and significant correlation with total tuber yield indicating that factors, which improve size of tubers, also have beneficial effect on total tuber yield. Yield as well as number of C grade tubers also had positive and significant correlation with total tuber yield. Relationship of total tuber yield with the yield and number of D (<25g) grade tubers was inconsistent. Total tuber yield had highly significant and positive relationship with total tuber number in both the experiments and during both the years indicating that factors that influence total tuber number also influence tuber yield. It may be concluded that weed population at early stages of crop growth can give indication of final tuber yield.